Day 3 Wed, March 08, 2017 2017
DOI: 10.2118/183983-ms
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drillstring Vibration Cyclic Loads on Wellbore Stability

Abstract: Wellbore instability resulted in the largest percentage of non-productive time (NPT) during drilling stage in oil industry. Wellbore instability during drilling includes: wellbore pack-off, excessive torque and drag, blowout, stuck pipe and other related well problems. Many studies assumed that wellbore instability problems were due to physical and chemical interactions between rocks and drilling fluid; and neglected impact of drillstring vibration on wellbore stability. Drillstring vibration is usually mitiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…The drill string vibration cyclic loads which are hitting the wellbore surface generate a decohesion in the preexisting wellbore natural fracture, then, the trend of the opening and closure of the wellbore natural fracture in function of the time also follows the trend of the drill string vibration oscillating profiles. Other studies in the literature have also highlighted the decohesion of the rock structure caused by the drill string vibration cyclic load [8,12,15]. The fluid pressure inside the fracture is highest near the wellbore, therefore, a la fracture width in that region is also expected.…”
Section: Development Of the Wellbore Natural Fracture For Different Cyclic Load Magnitude And Constant Number Of Cylic Loadsmentioning
confidence: 99%
See 2 more Smart Citations
“…The drill string vibration cyclic loads which are hitting the wellbore surface generate a decohesion in the preexisting wellbore natural fracture, then, the trend of the opening and closure of the wellbore natural fracture in function of the time also follows the trend of the drill string vibration oscillating profiles. Other studies in the literature have also highlighted the decohesion of the rock structure caused by the drill string vibration cyclic load [8,12,15]. The fluid pressure inside the fracture is highest near the wellbore, therefore, a la fracture width in that region is also expected.…”
Section: Development Of the Wellbore Natural Fracture For Different Cyclic Load Magnitude And Constant Number Of Cylic Loadsmentioning
confidence: 99%
“…Ref. [12] investigated the effects of the drill string vibration cyclic loads on the wellbore stability and they obtained slightly similar results with those of [8]. They found that wellbore failure occurred due to drill string vibration cyclic loads when: (i) the drill string vibration applied stresses on the formation exceeded the strength of the rock formation, (ii) the drill string vibration applied continuous cyclic loads on the wellbore resulted in the rock fatigue, (iii) the drill string generates cyclic loads which did not result in the rock fatigue, however, the strength of the rock reduced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that many activities, such as drilling, tunnel excavation, seismicity, geological energy exploitation and storage, and geological disposal of nuclear waste, can cause pore pressure to change, which may further change the structure and stress state of porous materials and may lead to shear failure or fracturing (Bruno and Nakagawa, 1991;Guayacán-Carrillo et al, 2017;Liu et al, 2013Liu et al, , 2020Mohajerani et al, 2012;Rice, 2006;Shi et al, 2021). In drilling engineering, there are many factors that can result in pore pressure variation near the wellbore, and these factors can be classified into physical (e.g., fluid flow into or out of the formation, time-dependent filter cake growth, capillary action, and hydrodynamic expansion), mechanical (e.g., drilling unloading, temperature change-induced thermal stress, and in-situ stressinduced stress concentration near the wellbore), chemical (e.g., interaction between the rock and drilling fluid), and engineering effects (e.g., surge/swab pressure during tripping operations, drill-string rotation or vibration, and the drill string colliding with the wellbore wall) (Jia et al, 2019;Khaled and Shokir, 2017;Ma et al, 2016;Meng et al, 2019;Roshan and Rahman, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Wellbore stability is affected by a variety of factors, such as mechanical impact as a result of drillstring vibration during drilling [6], formation material properties [7,8] and change in loading boundary conditions. Especially, with the exploration and development of unconventional energy resources such as shale gas/oil and geothermal energy, wells are being drilled deeper and at orientations with respect to the stress field that result in higher stress concentrations around the well.…”
Section: Introductionmentioning
confidence: 99%